Findings of Brain Imaging among Tuberculous Meningitis Patients: A Study of 30 Cases in Bangladesh - Shoab, Abul Kalam Mohammed; Hosen, Mostafa; Foez, Syed Abul; Wadud, Md Shaheen; Rahman, Habibur; Khan, Shahjada Mohammad Dastegir; Rana, Masud; Roy, Biplob Kumar (Bangladesh Journal of Infectious Diseases, 2019)
Background: Tuberculous meningitis is a serious health hazard and difficult to diagnose. Objectives: The purpose of the present study was to observe the role of CT/MRI in TBM diagnosis. Methodology: This was a retrospective study done from January 2010 to December 2011 for a period of two (02) years. Patients of TBM were reviewed in a medical college hospital of Bangladesh. Results: A total number of reviewed 30 TBM patients; among them 11 cases were confirmed TBM patients and 19 were probable patients. Brain imaging (CT/MRI) was performed in 15 cases. The use of brain imaging allowed the Brain lesions in 93.3% patients. Conclusion: Brain imaging was done in 15 out of 30 TBM patients and most of them (14/15) had got various forms of radiological abnormalities that aid in diagnosis and monitor of disease progression in TBM. Bangladesh Journal of Infectious Diseases, June 2019; 6(1):8-11